Study on health risk assessment of potentially toxic elements in the soil around landfill site in Shannan City, Tibet. Issue 1 (31st December 2022) - Zhou, Wenwu; Dan, Zeng; Zhou, Peng; Chen, Guanyi; Meng, Dean
ABSTRACT: This paper takes the soil around the Luqionggang landfill in Shannan city of Tibet Autonomous Region as the research object and studies the soil around the Luqionggang landfill by setting points and sampling. Then ICP-MS and AFS were used to analyze the contents of potentially toxic elements (PTEs) (Cu, Pb, Zn, Cr, Ni, Cd, As, Hg) in soil, and the health risk index method was used for risk assessment. The results showed that the primary exposure route of non-carcinogenic risk in the population was the oral route. And adults' HI value is 0.1692, which is less than children's HI value of 1.192, indicating that children are more affected than adults. Attention should be paid to the impact of PTEs As, Pb, and Cr in non-carcinogenic risk distribution. In the whole life cycle, the carcinogenic risk of the oral route is higher than that of the respiratory and skin contact routes.